Focus on sulfur count rates along marine sediment cores acquired by XRF Core Scanner. (21st July 2016) - Chéron, S.; Etoubleau, J.; Bayon, G.; Garziglia, S.; Boissier, A.
Abstract : The aim of this study is to investigate the information provided by sulfur count rates obtained by X‐ray fluorescence core scanner (XRF‐CS) along sedimentary records. The analysis of two marine sediment cores from the Niger Delta margin shows that XRF‐CS sulfur count rates obtained at the surface of split core sections with XRF‐CS correlate with both direct quantitative pyrite concentrations, as inferred from X‐ray powder diffraction (XRD) and sulfur determination by wavelength dispersive X‐ray fluorescence (WD‐XRF) spectrometry, and total dissolved sulfide (TDS) contents in the sediment pore water. These findings demonstrate the potential of XRF‐CS for providing continuous profiles of pyrite distribution along split sections of sediment cores. The potential of XRF‐CS to detect TDS pore water enrichments in marine sediment records, even a long time after sediment recovery, will be further discussed. Copyright © 2016 The Authors. X‐Ray Spectrometry Published by John Wiley & Sons Ltd.